1992
DOI: 10.1007/bf00224285
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HMW glutenin subunits encoded by chromosome 1A of bread wheat (Triticum aestivum L.) indicates quantitative effects on grain quality

Abstract: A gene encoding the high-molecular-weight (HMW) subunit of glutenin 1Ax1 was isolated from bread wheat cv Hope. Comparison of the deduced amino acid sequence with that previously reported for an allelic subunit, 1Ax2(*), showed only minor differences, which were consistent with both subunits being associated with good bread-making quality. Quantitative analyses of total protein extracts from 22 cultivars of bread wheat showed that the presence of either subunit 1Ax1 or 1Ax2(*), when compared with a null allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 216 publications
(94 citation statements)
references
References 22 publications
5
88
0
1
Order By: Relevance
“…Storage proteins, glutenins and gliadins, are synthesized in the endosperm during the grain-filling period; they comprise 90% of the protein in the wheat grain (Huebner and Wall 1974;Pike and MacRitchie 2004). High molecular weight (HMW) glutenin subunits each contribute about 2% of the total seed protein (Payne et al 1984;Halford et al 1992) and contribute the unique elastic properties and quality of bread dough.…”
Section: Introductionmentioning
confidence: 99%
“…Storage proteins, glutenins and gliadins, are synthesized in the endosperm during the grain-filling period; they comprise 90% of the protein in the wheat grain (Huebner and Wall 1974;Pike and MacRitchie 2004). High molecular weight (HMW) glutenin subunits each contribute about 2% of the total seed protein (Payne et al 1984;Halford et al 1992) and contribute the unique elastic properties and quality of bread dough.…”
Section: Introductionmentioning
confidence: 99%
“…Lines that have 5 HMW glutenin subunit genes expression contain about 10% of the protein in the form of HMW glutenin subunits. Each HMW glutenin subunit contributes about 2% of the total grain protein (Halford et aL 1992). The HMW glutenin proteins in wheat endosperm play an important role in bread-making quality (Payne et al 1980).…”
Section: Wheat Gluten Proteinsmentioning
confidence: 99%
“…Gupta and MacRitchie (1994) reported that the lDx5-lDylO HMW glutenin subunits had a greater effect on dough strength than !Dx2-lDyl2 HMW glutenin subunits. Halford et al (1992) reported that the lAxl HMW glutenin subunit is also associated with good quality of bread wheat flour.…”
Section: Bread-making Qualitymentioning
confidence: 99%
See 2 more Smart Citations